Tegula romana из поселения Козырка близ Ольвии (к вопросу о римской строительной традиции в Северо-Западном Причерноморье) - Сон, Н.А.; Буйских, А.В. (Археологія і давня історія України, 2014)
Статья представляет собой публикацию и интерпретацию уникального декоративного кирпича
из раскопок А.В. Буракова на поселении ольвийской хоры Козырка-1. Статтю присвячено публікації та інтерпретації
унікальної обпаленої цеглини з поселення ольвійської хори Козирка-1. The article is devoted to the publication and interpretation
of a unique burnt brick from Kozyrka-1 settlement
at Olbian chora. Engobed facial side of the brick
is decorated by circular incised ornament in the form of
six-petal rosette covered by dark red paint (ochre); big
irregular dots between the petals are made by this paint
as well. In this occasion, the point is that the defective
ceramic product was reused, though with different purpose,
which is frequently recorded during the excavations
at the Ancient Greek sites. The form and size of
other burnt bricks from Kozyrka with narrow sides
painted with dark red ochre allow the authors to assume that a fragment of a brick with rosette was not defected, but was a fractional product. It is likely that the decoration was incised and painted during the erecting of the building. The brick with a red rosette had its functional
purpose, most probably for wall decoration in the interior or for facade decoration of a building.